A fast search and classification method of isomorphic polygons in LSI design data using geometric invariant feature value. (2016) - Shoji, Shuji; Koyama, Akio
A large number of isomorphic polygons are included in design data of LSI. Fast search and classification for isomorphic polygons are expected for compactness and fast pattern search of design data. In this paper, we propose a high speed and high accuracy classification method of isomorphic polygons. The proposed method can reduce a shape comparison process significantly by using a geometric invariant feature value for a polygon. The feature value is calculated by summation of distance from centre of gravity to each vertex, and a polygon contour length. This value does not be affected by parallel shift, rotation and reduced scale. The feature value is same among isomorphic polygons and it is possible to access an isomorphic polygon group quickly by using this value. From evaluation results, we verified that the proposed method can realise fast classification for isomorphic polygons, and compactness of design data.